Effectiveness of internet-delivered therapist supported acceptance and commitment therapy intervention in the treatment of depression, anxiety and stress on university students - Järvisalo, Sameli (2015)
The present study investigates the effectiveness of a 5-week internet delivered ACT-based intervention in the treatment of depression, anxiety and stress in university students. Randomized controlled design was used and 31 students from the University of Jyväskylä were stratified into groups by age, sex and severity of their condition and then randomized into two groups: experimental group and wait list control group. 14 psychology students from the psychology department of the University of Jyväskylä were trained as support-personnel. Wilcoxon’s matched pairs test was used for the examination of the changes occurring within the groups in the RCT as well as the delayed treatment of the control group. Mann-Whitney U-test was used to examine statistical differences between the groups at baseline and after the treatment as well as in comparing the two treated groups at their respective baseline. Results of the study showed that the provided intervention produces statistically significant enhancements in well-being and stress, and that the increase was due to the intervention since similar increases were not found in the wait-list condition. Furthermore, well-structured ACT-based interventions with minimal face-to-face time have low demands for therapists experience – therefore they offer safe and effective opportunities for beginning therapists to practice their professional skills with a low risk for the person being treated. Results also support previous research findings on the effectiveness of both internet-delivered interventions as well as ACT-based treatments. Further research is called for to recognize the factors in participants and in intervention protocol influencing intervention effectiveness, acceptability and participant commitment towards internet delivered treatment. Also, further research would be required to recognize the possible subgroups of participants, who would benefit most from the described intervention. A longer intervention design with a larger sample size and a quantitative focus on the participants’ use of intervention content would allow a more in-depth investigation of correlations between the use of content and the occurring changes in process measures and these effects in relation to both intervention progress and outcomes. Described research endeavors would bring further insight and knowledge for the advantage of future intervention development.